The Role Of Educational Environment In Academic Stress: The Mediating Effects Of Self-Efficacy And Social Support Among University Students - Kurnia Khafidhatur Rafiah; Sulwani Husna Afrizal (CV Putra Publisher, 2026)
This study examines the role of the educational environment in academic stress among university students, focusing on the mediating effects of self-efficacy and social support. A total of 106 undergraduate students from universities in Indonesia participated in an online survey measuring educational environment, self-efficacy, social support, and academic stress. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that the educational environment has a significant positive effect on self-efficacy (β = 0.640, p < .001) and social support (β = 0.590, p < .001) but does not directly reduce academic stress (β = −0.095, p = .24). Self-efficacy has a significant negative effect on academic stress (β = −0.219, p = .002), whereas social support does not show a significant effect (β = 0.045, p = .494). The indirect effect of the educational environment on academic stress through self-efficacy is significant (β = −0.141, p = .019), while the indirect path through social support is not. The model explains a small portion of the variance in academic stress (Adjusted R² = 0.041; Q² = 0.027), indicating the presence of other relevant stressors beyond the educational environment. These findings highlight the importance of fostering self-efficacy within supportive educational environments to help students cope with academic stress.